MODERNIZATION IN THE CONTEXT OF GLOBAL CHALLENGES AND NATIONAL INTERESTS (Journal of Philosophy, Culture and Political Science, 2023)
The article studies modern approaches to the theory of modernization and its reconciliation with the realities of the current world. A critical analysis of postmodernization and postmodern state, which is presented as an alternative to modernization, is given, and it is claimed that it is no more sustainable and efficient in the face of global challenges. A brief look at the modernization models of Azerbaijan, Turkey, Kazakhstan and China is given, and it is stated that the modernization process serves the purpose of reaching the level of development of advanced countries without jeopardizing national interests and values. In some cases, global crises make it necessary to accelerate modernization processes, especially political modernization, and carry out reforms in order to increase the efficiency and flexibility of state institutions against the background of changing socio-economic requirements. The fact that the principles of Western liberal democracy are in the leading position in international law and the charters of a number of international organizations, and their indoctrination to developing countries, in some cases contradicts the national interests of those countries. Therefore, while determining the path of development, besides referring to foreign experience each state should focus on its national interests and rely on its national characteristics.Key words: modernization, postmodernization, development, global challenges, national interests